Training on writing COVID-19 slogans for teens and basic food assistance for angkot drivers affected by the pandemic - Amalia, Nur; Nawawi, N.; Puspitasari , Nur Aini (Universitas Muhammadiyah Malang, 2021)
Activities to implement one of the Tridharma Perguruan Tinggi to continue to share knowledge and share basic needs with communities affected by COVID-19 need to be done. This activity aims to provide training in writing COVID-19 slogans for adolescents and providing groceries for Ciputat-Parung Angkot Drivers who are affected by COVID-19. The activity was held in May 2020. The activity was carried out well and was welcomed by the community. This is evidenced by the enthusiasm of teenagers in writing COVID-19 slogans and being able to foster a spirit of creativity and productivity so that they can raise awareness of teenagers.